PENGARUH RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018 – 2023 - Hasbi Wibisono, Faraz; Agusentoso, Randhy (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Return on Equity (ROE) and Earning Per Share (EPS) on Stock Prices in Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2023. The research methods and types of data used in this study are quantitative and secondary data in the form of financial statements. The population in this study is Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange 2018 – 2023. The sample in this study is 8 companies using the purposive sampling method. The analysis methods used are descriptive statistical tests, data panel regression analysis and classical assumption tests. For hypothesis testing, it is carried out by significance tests, namely the T test and the F test with the help of Eviews 13 software. The results of this study show that the Return On Equity variable partially has a significant effect on stock prices. Meanwhile, Earning Per Share partially has a significant effect on stock prices. Then simultaneously showed that the variables Return On Equity and Earning Per Equity Ratio had a positive and significant effect on the stock price with a value of Fcal 20.07421 > Ftable 3.20 with a coefficient value of 59%, the remaining 41% was influenced by variables outside of this research.